Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The solution of the equation

$\sqrt{(x+1)} -\sqrt{(x-1)}= \sqrt{(4x-1)}$

is $\frac{5}{4}$,but when we put $x=\frac{5}{4}$ in the given equation, then it does not satisfy the equation.

Actually, if we take $f(x)=\sqrt{(x+1)} -\sqrt{(x-1)} -\sqrt{(4x-1)}$ then we can see that $f(x)$ is defined when $x \geq 1$ and $f(1) \geq 0\mbox{ and }f'(x) \geq 0$ so, the function is monotone increasing and it will never appear zero.

so, my question is , In this type of equation where the solution actually does not exist, then why should we get this type of solution?

my solution procedure is, $$ \begin{align} \sqrt{(x+1)} -\sqrt{(x-1)}&= \sqrt{(4x-1)}\\ \implies 2x-2\sqrt{x^2-1}&=4x-1\\ \implies {-2}\sqrt{x^2-1}&= 2x-1\\ \implies 4(x^2-1)&=4x^2+1-4x\\ \implies x&=5/4 \end{align}$$

share|cite|improve this question
As you wrote it, $f(x)$ is monotone decreasing with $f(1) <0$ – Claude Leibovici Feb 22 '14 at 6:09
$f(x)$ is not defined when $x < 1$ – ROBINSON Feb 22 '14 at 6:12
process your solution procedure in reverse order: substitute your solution for x in the equation. when it first hapens that it is not a solution then figure out what happened – miracle173 Feb 22 '14 at 6:27
In simple words, square the equation only when you know the signs of both sides are the same. Only when both sides satisfy one of $\ge 0$, $\le 0$ together can you square the equation. $(-1)^2=1^2$, e.g., doesn't imply that $-1=1$. Let the equation you've squared be $LHS=RHS$. The case when $LHS=RHS$ in this case is impossible, so squaring, instead of showing you two solutions, one of which is correct and the other one that doesn't satisfy $LHS=RHS$, brings you only one solution. That is, the solution to $-LHS=RHS$. Hence $x=\frac{5}{4}$ satisfies $-LHS=RHS$ only, which is not what you want. – user26486 Feb 22 '14 at 15:30
Your assertion that $f(1)\geq 0$ is false. $f(1) = \sqrt{2} - \sqrt{0} - \sqrt{3}$ and $\sqrt{2} -\sqrt{3}<0$. – Glen_b Feb 22 '14 at 23:54
up vote 16 down vote accepted

Let's consider a more simple example, to understand. Given the equation $$ x = 1 $$ you can take the square of both sides: $$ x^2 = 1 $$ and find two solutions: $$ x=1 \qquad x=-1. $$

This happens because the operation $x\mapsto x^2$ is not invertible. If you apply a non invertible function to an equation, the number of solutions might increase.

share|cite|improve this answer

$-\frac{x}{x}= \frac{x}{x}$ has no solutions at all, since $-\frac{x}{x}\neq \frac{x}{x}$ no matter what $x$ is.

But we can square both sides, and then what happens?

$\frac{x^2}{x^2}= \frac{x^2}{x^2}$ is an equation that is true for all nonzero numbers.

By applying a non-invertible operation to both sides, we can turn an equation with no solutions into one with uncountably infinitely many solutions.

share|cite|improve this answer

The process of solving an equation is basically that of inversion: you successively apply (inverse) functions to both sides of the equation until you reach a point where the solution is clear. This process depends on each successive equation (upon applying various inverses successively) being equivalent to the previous one so that the final equation $x=\ldots$ is equivalent to the original equation. However, when you apply non-invertible operations (such as $x\mapsto x^{2}$, i.e. squaring both sides), you don't get an equivalence between the equation before squaring and the equation after squaring: you get a forward implication, which is to say that the final equation $x=\ldots$ does not imply the previous equation(s) prior to squaring, it is only implied itself by the previous chain of equations.

share|cite|improve this answer

Whenever we square, we immediately introduce extraneous root

Observe that $\displaystyle\frac54$ is actually a root of $$\sqrt{x+1}=\sqrt{4x-1}-\sqrt{x-1}$$

Also, observe that $\displaystyle2x-1=-2\sqrt{x^2-1}\le0\implies 2x\le1\iff x\le\frac12$ for real $x$

But, $\displaystyle{\sqrt{x-1}}$ is not real unless $x\ge1$

share|cite|improve this answer

Write the equation as $$ \sqrt{x+1}=\sqrt{x-1}+\sqrt{4x-1} $$ Then you must have \begin{cases} x+1\ge0\\ x-1\ge0\\ 4x-1\ge0 \end{cases} which boils down to $x\ge1$. Now square, you're sure not to add spurious solutions, because both sides represent non negative numbers: $$ x+1=x-1+4x-1+2\sqrt{(x-1)(4x-1)} $$ or $$ -4x+3=2\sqrt{(x-1)(4x-1)} $$ Now the right hand side is non negative, so also the left hand side must be, which means $$ -4x+3\ge0 $$ or $x\le 3/4$. With the previous limitation, this has the consequence that no solution can exist.

share|cite|improve this answer

An equation $F(x)=0$ is an implicit way of defining a set $S$. What we want is an explicit presentation of $S$, say, a list $S=\{a,b,c\}$.

Algebraic manipulations of the form $$F(x)=0\quad\Rightarrow \quad G(x)=0\quad\Rightarrow\quad\ldots\quad\Rightarrow \quad x\in S'\ ,\tag{1}$$ where $S'$ is a certain finite list (or similar object) do not prove that $S=S'$. They only prove that each $x\in S$ also is in $S'$, in other words: Such manipulations only prove $S\subset S'$. When $S'$ is a finite set it is usually simple to decide which $x\in S'$ are actually solutions of the original problem.

When the arrows in $(1)$ are reversible, i.e. can be replaced by $\Leftrightarrow$'s with no harm done, then we of course have $S'=S$, and no extra verification is necessary.

Another instance where $S'$ is automatically the correct solution set is the following: The given equation $F(x)=0$ is of a type for which we have a general theory guaranteeing "exactly two solutions" (as in the case of a quadratic equation) or "exactly one solution", or "a solution space of dimension $d$". When the $S'$ found in $(1)$ satisfies the requirements promised by the general theory then automatically $S'=S$.

share|cite|improve this answer

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle #1 \right\rangle} \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace} \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left( #1 \right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ Indeed, you are solving $\large 4!!!$ equations due to the 'squaring' in your procedure: $$ \root{x + 1} \pm \root{x - 1} = \pm\root{4x - 1} $$ For example, $x = 5/4$ satisfies $\root{x + 1} + \root{x - 1} = \root{4x - 1}$ since $$ \root{{5 \over 4} + 1} \color{#f00}{\Large +} \root{{5 \over 4} - 1} = {3 \over 2} + \half= 2= \color{#f00}{\Large +}\root{4\times{5 \over 4} - 1} $$

share|cite|improve this answer
$10 \uparrow (10 \uparrow (10 \uparrow 1.4))$ equations – Hugh Sep 16 '14 at 5:44

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.